(untitled) (Fiep Bulletin - online, 2017)
The Amazon region is rich in natural and cultural biodiversity, rich fauna and flora, with a culture based on indigenousand riverside issues. All this socio-historical setting is crucial to a human stereotype that looks like a caricature of what they reallyare. Nowadays, the man from the Amazon region does not refer to the Indian figure or the riverside any longer; his human materialis rich in multiple cultures that have settled there, and merged to the local culture, which has created a third persona. In order notto lose their regional characteristics, these people have adopted a modus vivendi where man, nature, technology and thecontemporary walk along, making up a peculiar profile. For these people, this is recreated every day, and existing features areborn with so many other faces of the lands. In sport, the same phenomenon takes place: the Caboclo (indigenous person) profilemerges the profile of athletes and sportsmen; such affinity with the regional body culture that presents a rich gesture vocabularyexperiences and everyday experiences. In this essay, such issue is addressed: a reflection on human development from thesport practiced in the Amazon region; the premise of sustainable development and quality of life.